Breaking The Limitations of Distribution: Creating an Integrated Solution with Saving Matrix and Net Present Value - Astari, Alifah Nur; Fauzi, Muchammad (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
PT BCD is one of the large pharmaceutical companies in Bandung, West Java which plays the role of main distributor. PT BCD is facing a problem related to its company logistics. The problem in question is in the form of customer complaints that reflect a bad image for the company, especially regarding on-time delivery. Many of these complaints came from outlets in the central rayon area consisting of RS A, RS B, RS C, Pharmacy D, Pharmacy E, Pharmacy F, PBF G, PBF H, and PBF I. In an effort to overcome this problem, the management plans to launch a program called same-day delivery service so it is necessary to carry out research that integrates the saving matrix method to determine the most optimal distribution route for pharmaceutical products so that the distance traveled in delivery is the shortest as well as carrying out mathematical considerations regarding fleet investment decisions based on which offers are available. Provides the greatest savings using the total cost of ownership (TCO) net present value method approach. From the results of the analysis of the two integrated methods, a picture of the decision in the form of the most optimal route based on the saving matrix analysis is obtained, namely PT BCD – RS A – RS B – PBF G – PBF H – PBF I – Apotek F – RS C – Apotek E – Apotek D – PT BCD with the decision to procure a fleet in the form of purchasing an L300 type box car. Keywords: Logistic, Net Present Value, Same Day Delivery, Saving Matrix